Caracterización del aceite esencial de eneldo (Anethum graveolens), en función de la composición química, capacidad antioxidante y actividad antimicrobiana. - Quevedo Analuisa, Marjorie Aracely (2022)
The present research was carried out in the Agroindustries laboratory of the Faculty of Agricultural Sciences and Natural Resources (CAREN) of the Technical University of Cotopaxi, where the extraction of essential oil from dill (Anethum graveolens) was characterized based on the chemical composition, its antioxidant capacity and antimicrobial activity, the steam distillation method was used using a "XIAOJIAN" brand equipment (Lanphan Ltd., China), the statistical analysis was performed by surface design - response using the Design Expert 8.0.6 program, 17 experimental runs were produced and the study factors were time (60, 90, 120 min) and the mass/solvent ratio (1:3; 1:4; and 1:5 g/L). The results obtained for the essential oil yield were 1.3834 % in a proportion of 1:5 g/l and a time of 120 minutes. The analysis of the chemical composition was carried out through gas chromatography coupled to a mass spectrometer detector in the Agilent Technologies equipment model: 7890ª GC System coupled to a 5975C inert XLMSD with Triple-Axis Detector mass selective detector, where reported the presence of 10 chemical compounds present in the essential oil whose main components were: Estragole (77.18 % w/v), Trans-Anethole (8.73 % w/v) and Alpha-Phellandrene (5.65 % w /v), the antioxidant capacity was 240.01 2+/g for the FRAP assay and 270.14 TE/g for the ABTS assay, for antimicrobial activity it was evidenced with 0.5 mg/L of inhibition for Escherichia coli ATCC 25922 and Pseudomonas aeruginosa ATTC 39327